2002
DOI: 10.1103/physrevd.65.044022
|View full text |Cite
|
Sign up to set email alerts
|

Bounding the mass of the graviton using binary pulsar observations

Abstract: The close agreement between the predictions of dynamical general relativity for the radiated power of a compact binary system and the observed orbital decay of the binary pulsars PSR B1913+16 and PSR B1534+12 allows us to bound the graviton mass to be less than 7.6 × 10 −20 eV with 90% confidence. This bound is the first to be obtained from dynamic, as opposed to staticfield, relativity. The resulting limit on the graviton mass is within two orders of magnitude of that from solar system measurements, and can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(209 citation statements)
references
References 19 publications
11
197
0
1
Order By: Relevance
“…Here ℓ P and M P are Planck length and mass respectively. Current observational bounds on the graviton mass from solar system measurements is m g < 4.4 × 10 −22 eV and its accuracy could be lowered up to m g < 10 −26 eV from future gravitational wave measurements [33,34,35,36]. Thus, our estimated theoretical value of the 'effective graviton mass' is well below the observational bound at present.…”
Section: Holonomy Correctionsmentioning
confidence: 69%
See 1 more Smart Citation
“…Here ℓ P and M P are Planck length and mass respectively. Current observational bounds on the graviton mass from solar system measurements is m g < 4.4 × 10 −22 eV and its accuracy could be lowered up to m g < 10 −26 eV from future gravitational wave measurements [33,34,35,36]. Thus, our estimated theoretical value of the 'effective graviton mass' is well below the observational bound at present.…”
Section: Holonomy Correctionsmentioning
confidence: 69%
“…This equation (35) describes propagating degrees of freedom which are the usual gravitational waves subject to quantum corrections. Unlike for inverse densitized triad corrections, the coefficients ofḧ i a and ∇ 2 h i a take the classical form.…”
Section: Linearized Equationmentioning
confidence: 99%
“…For example, if the dispersion measure of a massive graviton is assumed, GW150914 places an upper limit of mgc 2 < 2.2×10 −22 eV on the mass mg of the graviton ([64]; see [77] for the original proposal of this idea). This is significantly better than the limits available from Solar System [78] or binary pulsar [79] tests, and is also better than the limits that can be obtained by the lack of gravitational Cerenkov slowing of high-energy cosmic rays in certain parameter regimes [80]. There are slightly stronger, but more model-dependent, limits on the graviton mass that can be placed by the existence of stellar-mass black holes [81].…”
Section: Tests Of Gravity With Gw150914mentioning
confidence: 80%
“…Ryan [15] has outlined how observations of the gravitational radiation from capture orbits of solar mass compact bodies about a supermassive black hole may allow the determination of certain multipole moments of the central hole, thereby testing the prediction of general relativity. More recently, Will [16] and Finn and Sutton [17,18] have described tests of general relativity that bound the mass of the graviton, and Scharre and Will [19] and Fairhurst et al [20] have shown how gravitational-wave observations of pulsars may be used to bound the value of the Brans-Dicke coupling constant.…”
Section: Introductionmentioning
confidence: 99%
“…One set of tests, including [13,15,17,19], is based on energy conservation arguments: the observed evolution of a system or of the radiation from a system is related to the energy loss expected owing to the radiation. A second class of tests [12,14,20] focuses on the observed polarization modes of the field.…”
Section: Introductionmentioning
confidence: 99%